Hill & valley log cabins - DeCarli, Robert (American Quilter's Society, 2013)
"Author shows how to use rectangles to make curved log cabin blocks along with using color and value to create optical illusions. 13 projects from wallhangings to bed quilts with graphic, geometric designs for a modern look"--Provided by publisher.